If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 4) + -6(2x + -6) = 4x + -16 Reorder the terms: (4 + 3x) + -6(2x + -6) = 4x + -16 Remove parenthesis around (4 + 3x) 4 + 3x + -6(2x + -6) = 4x + -16 Reorder the terms: 4 + 3x + -6(-6 + 2x) = 4x + -16 4 + 3x + (-6 * -6 + 2x * -6) = 4x + -16 4 + 3x + (36 + -12x) = 4x + -16 Reorder the terms: 4 + 36 + 3x + -12x = 4x + -16 Combine like terms: 4 + 36 = 40 40 + 3x + -12x = 4x + -16 Combine like terms: 3x + -12x = -9x 40 + -9x = 4x + -16 Reorder the terms: 40 + -9x = -16 + 4x Solving 40 + -9x = -16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 40 + -9x + -4x = -16 + 4x + -4x Combine like terms: -9x + -4x = -13x 40 + -13x = -16 + 4x + -4x Combine like terms: 4x + -4x = 0 40 + -13x = -16 + 0 40 + -13x = -16 Add '-40' to each side of the equation. 40 + -40 + -13x = -16 + -40 Combine like terms: 40 + -40 = 0 0 + -13x = -16 + -40 -13x = -16 + -40 Combine like terms: -16 + -40 = -56 -13x = -56 Divide each side by '-13'. x = 4.307692308 Simplifying x = 4.307692308
| 140+2x=1250 | | 1.8T=-72 | | 2x-140=1250 | | 6(3-h)=8h-10 | | 140-2x=1250 | | 9x+2=-7x-126 | | 0.20x+0.05(10-x)=0.10(32) | | 33=N+37 | | d^2-3d=6 | | (2m-5)x^2+mx+7=0 | | -16-p+12=26 | | 45xy-72zw=0 | | 17+2.66=30 | | z+31=26 | | cos(2x+1)=.3 | | cos(2x+1)=5 | | 3.5=x-9.9 | | 2(8)-3(5)+9= | | 3x^2+5=4x+4 | | 12x^2-216x+585=0 | | (8)-3(5)+9= | | 2m+3n=14-n | | 7+x=35 | | 2(x+3)^2=30 | | 0.555555556+0.416666667d=0.916666667+0.777777778d | | 4q-3=45 | | 18x+6=3(2x+6x) | | 3log(x)=6 | | (u-2)(u^2+2u+4)-3u+8=0 | | 0=16t^2+144 | | 6x^2=126 | | 12x+28x^3=0 |